Unusual Market Activity Announcements: A Study of Price Manipulation on the Indonesian Stock Exchange - Hanafi, Mamduh M. (Gadjah Mada International Journal of Business, 2010)
We investigate stocks involved in the Unusual Market Activity (UMA) Announcements. The Indonesian Stock Exchange occasionally issues UMA announcements when it suspects that there are unusual price increases (positive UMAs) or price decreases (negative UMAs), as well as unusual increases in trading volumes. We believe that UMA announcements signal a high probability that stocks are being manipulated. We find no differences in fundamentals and trading variables between stocks in the UMA announcements and those not in the UMA announcements. Any stock is vulnerable to market manipulation. Stocks in the UMA announcements do not exhibit reversal patterns, suggesting that price effect is permanent. UMAs seem to convey relevant information, which is most likely in the form of insider type of information.Keywords: emerging market; price manipulation; unusual market activity announcement.